THE PROBLEM FACING BY PT. METRO BATAVIA TO PROVIDE COMPENSATION TO COSTUMERS BASED ON THE CONSTITUTION (A case study concerning Bankruptcy of PT. Metro Batavia) - Tito Sofyan; Candra Irawan; Dya Vitalia (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
Bankruptcy happened to airlines companies causes troubles not only on debtors but also on consumers as the expectant passengers that have purchased flight tickets. When PT. Batavia Air was sentenced bankruptcy by the Commerce Court then all operational activities shall stop. These halted Operational activities resulted loss on consumers since thousand of consumers that have bought tickets cannot fly. Verdict of Commercial Court of Jakarta Pusat No.77/Pailit/2012/PN.NIAGA.JKT.PST on January 30th, 2013 decided all activities concerning on properties are delegated to curator appointed by the court stated on verdict. For consumers that demand any compensation of loss, it is suggested to register a debt note in curator office. On Act No. 1 of 2009 concerning on airlines and Minister Regulation No. 77 of 2011 concerning responsibility of airline, it is stated that airlines are responsible to repay the whole cost of ticket spent by passengers. However, in the reality it is impossible to consumers to get the compensation since they stand as concurrent creditors which have no rights to get advanced repayment. The full repayment can only be possible to gain by consumers after curator complete the whole repayment process to separative and preference creditors.